An evaluation of partnership for productive development in Brazil's healthcare - De Magalhães, Jorge Lima (2018)
21st Century brings great challenges in the information and knowledge areas. The public health is intensified in Developing and Less Developed Countries on account of parasitic diseases as well as developed countries because emerging and reemerging diseases. This diseases associated with chronic or acute diseases can intensify causing a serious health problem as drugs resistance, neglected disease and to afford perpetuate poverty. Thus, it is urgent new ways for information management. The management of the Partnership for Productive Development (PDP) have been shown a promising tool to help internalize new technologies and foster R,D&I. This chapter gives an evaluation for Healthcare using the example of the Brazilian PDP whose last way may be considered as a Knowledge Translation. In five years were conducted 103 PDP involving public and private pharmaceutical companies and international producer, promoting the development of local economy and reducing government spending from medicines derived from PDP.